2020
DOI: 10.1111/jsr.12969
|View full text |Cite
|
Sign up to set email alerts
|

Poor sleep quality associates with self‐reported psychiatric and cardiometabolic symptoms independently of sleep timing patterns in a large sample of rural and urban workers

Abstract: Summary Poor sleep associates with mental and cardiometabolic pathological outcomes. The participation of sleep timing features in the pathways by which this relationship occurs is not clear. This study aims to evaluate the interrelationship between sleep quality and self‐reported psychiatric/cardiometabolic symptoms, considering mediation and moderation effects of sleep timing patterns, and urban versus rural work environment, respectively; and to verify the association between sleep quality and polymorphisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Second, data on obstructive sleep apnea(OSA) was not collected in the current study. A very recent study has shown that the association between OSA and impaired lipid pro le is partly determined by genes [36]. However, snoring status was adjusted as an alternative confounder, since patients with OSA often have symptoms of snoring status.…”
Section: Study Limitationmentioning
confidence: 99%
“…Second, data on obstructive sleep apnea(OSA) was not collected in the current study. A very recent study has shown that the association between OSA and impaired lipid pro le is partly determined by genes [36]. However, snoring status was adjusted as an alternative confounder, since patients with OSA often have symptoms of snoring status.…”
Section: Study Limitationmentioning
confidence: 99%
“…The retinoic acid receptor-related orphan receptor A (RORA) gene is known to play a key role in circadian rhythm and sleep disorders ( Möller-Levet et al, 2013 ) and was considered as a promising candidate gene for regulating sleep duration ( Carvalho et al, 2020 ; Hou et al, 2020 ) and sleep latency ( Kripke et al, 2015 ). De novo dominant toxic RORA gene variants have found to be associated with ataxia and cerebellar atrophy ( Guissart et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%